PENGARUH STRATEGIC LEADERSHIP TERHADAP COMPETITIVE ADVANTAGE MELALUI ORGANIZATIONAL LEARNING SEBAGAI VARIABEL INTERVENING - Erlinda Lios (Business Accounting Review, 2015)
This study aimed to analyze the influence of strategic leadership to the competitive advantage through organizational learning. This study used primary data from questionnaires which were distributed to 60 company managers in Surabaya. The data collected analyzed by using Partial Least Square (PLS) software to test the hypothesis. The results showed that there were positive significant correlation of the strategic leadership to competitive advantage, strategic leadership to organizational learning, organizational learning to competitive advantage, but organizational learning is not an intervening variable between strategic leadership and comoetitive advantage.